EFFECTIVE STRATEGIES FOR PASSING THE TOPIK EXAM (International journal of artificial intelligence, 2025)
This article discusses effective strategies for preparing and succeeding in the Test of Proficiency in Korean (TOPIK) exam. It highlights key approaches such as structured study plans, understanding exam formats, focusing on vocabulary and grammar, practicing past papers, and utilizing modern technology. The article emphasizes how these methods help learners enhance their language skills and improve their chances of passing the TOPIK exam efficiently.